State of knowledge on biology and ecology of field bugs of the genus Lygus Hahn, 1833 (Hemiptera: Heteroptera: Miridae) in agrocenoses of Ukraine and the world - Rysenko, M. M. (The Kharkiv Entomological Society Gazette, 2022)
Lygus bugs (Lygus Hahn, 1833) are omnivorous pests of great economic importance in field crop rotations. The bugs L. rugulipennis (Poppius, 1911) and L. pratensis (Linnaeus, 1758) are part of the permanent complex of pests of sunflower, soybean, pea, wheat and winter barley, berry crops in Ukraine. The article analyzes literary data devoted to the features of biology and ecology of field bugs. Particular attention is paid to the issues of species composition and seasonal changes of fodder plants of field bugs, their harmfulness, natural enemies, agroecological approaches in the regulation lygus bugs’ populations. Data from studies conducted in European countries, North America, and China are presented. 83 refs.